On three new Orchestina species (Araneae: Oonopidae) described from China - Liu, Keke; Xiao, Yonghong; Xu, Xiang (Zootaxa, 2016)
Three new species of oonopid spider from China are diagnosed, described and illustrated: Orchestina apiculata sp. nov. from Hunan, O. bialata sp. nov. and O. multipunctata sp. nov. from Jiangxi. The total number of the known species of Orchestina from China rises to 11 with the addition of three new species described in the present paper. Relationships with Asian and Afrotropical representatives are discussed.